2009
DOI: 10.1007/s00415-009-5389-7
|View full text |Cite
|
Sign up to set email alerts
|

Social and clinical determinants of quality of life in Parkinson’s disease in Austria: a cohort study

Abstract: Parkinson's disease (PD) is associated with a reduction of health-related quality of life (HrQoL). Demographic and clinical determinants of HrQoL in PD have been previously investigated, but less is known about its social determinants. Data on HrQoL in Austrian patients with PD are not available. The objective of this cross-sectional survey was to evaluate HrQoL of Austrian patients with PD and to provide a comprehensive analysis of its social and clinical determinants. Outpatients (n = 100) with idiopathic PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 38 publications
5
34
0
Order By: Relevance
“…Another social parameter positively associated with HrQoL was the number of people in the patient's household. Interestingly, this finding corresponds well with results of studies in idiopathic PD [6] . Similarly, as in idiopathic PD, we suggest that a higher number of people in the household improves the availability of home care provided by family members (informal care).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Another social parameter positively associated with HrQoL was the number of people in the patient's household. Interestingly, this finding corresponds well with results of studies in idiopathic PD [6] . Similarly, as in idiopathic PD, we suggest that a higher number of people in the household improves the availability of home care provided by family members (informal care).…”
Section: Discussionsupporting
confidence: 82%
“…Representing the impact of a disease on a person's self-perceived well-being, HrQoL is an important aspect in the healthcare of chronic diseases such as neurodegenerative disorders. The majority of studies evaluating HrQoL in parkinsonian disorders concentrated on idiopathic PD [6][7][8][9][10][11][12] and only a few investigated APS [15,16,18,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the HRQoL related to mental health is more severely impaired in neurodegenerative diseases (e.g. Parkinson's disease, Huntington's disease) [3,17,40,44,45]. In our study, the HRQoL as measured by the SF-36 was most affected in ALS and least affected in MG. Padua et al [31] investigated the HRQoL in MG and found much lower scores in the domains of the SF-36.…”
Section: Discussionmentioning
confidence: 53%
“…Depression was also found to be an important determinant of the HRQoL in other chronic neurological diseases, such as Parkinson's disease and Huntington's disease [3,17,40,44,45]. Interestingly, age was among the independent HRQoL-predictors in MG but not in ALS.…”
Section: Discussionmentioning
confidence: 88%